Clinical characteristics, time course, treatment and outcomes of patients with immune checkpoint inhibitor-associated myocarditis - Edward J Spangenthal; Igor Puzanov; Marc S Ernstoff; Pankit Vachhani; Fumito Ito; Ankita Kapoor; Benjamin Switzer; Poornima Subramanian; Yan V Yatsynovich; David M Jacobs; Maya R Chilbert; Umesh C Sharma; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICI) have emerged as a front-line therapy for a variety of solid tumors. With the widespread use of these agents, immune-associated toxicities are increasingly being recognized, including fatal myocarditis. There are limited data on the outcomes and prognostic utility of biomarkers associated with ICI-associated myocarditis. Our objective was to examine the associations between clinical biomarkers of cardiomyocyte damage and mortality in patients with cancer treated with ICIs.Methods We retrospectively studied 23 patients who developed symptomatic and asymptomatic troponin elevations while receiving ICI therapy at a National Cancer Institute-designated comprehensive cancer center. We obtained serial ECGs, troponin I, and creatine kinase-MD (CK-MB), in addition to other conventional clinical biomarkers, and compared covariates between survivors and non-survivors.Results Among patients with myocarditis, higher troponin I (p=0.037) and CK-MB (p=0.034) levels on presentation correlated with progression to severe myocarditis. Higher troponin I (p=0.016), CK (p=0.013), and CK-MB (p=0.034) levels were associated with increased mortality, while the presence of advanced atrioventricular block on presentation (p=0.088) trended toward increased mortality. Weekly troponin monitoring lead to earlier hospitalization for potential myocarditis (p=0.022) and was associated with decreased time to steroid initiation (p=0.053) and improved outcomes.Conclusions Routine troponin surveillance may be helpful in predicting mortality in ICI-treated patients with cancer in the early phase of ICI therapy initiation. Early detection of troponin elevation is associated with earlier intervention and improved outcomes in ICI-associated myocarditis. The recommended assessment and diagnostic studies guiding treatment decisions are presented.